Penentuan Harga Jual Rumah Subsidi melalui Akad Murabahah pada PT. Bank NTB Syariah Kantor Cabang Pejanggik - Lalu Adiyatma Taopikul Hadi; Junaidin; Dony Hidayat (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Although it has not even been 3 years of cooperation, there have been many customers who have completed the murabahah KPR contract at Bank NTB Syariah, which is specifically located in Grand Muslim Housing, Terong Tawah. This research aims to determine the selling price of subsidized houses through a murabahah contract at PT. Sharia NTB Bank. This type of research is descriptive qualitative, the location and research information is taken purposively (designated), that is, those who are considered to be related to certain characteristics. The research was conducted at Bank NTB Syariah KC Pejanggik. The informants in this study were the leaders of Bank NTB Syariah KC Pejanggik, employees, and customers of KPR FLPP who made financing at PT Bank NTB Syariah. The research method used in this study consisted of observation, interviews, and documentation. Meanwhile, data analysis techniques are arranged through data collection, data reduction, data display, and verification. The results of this study indicate that 1). the determination of the subsidized home selling price (FLPP) at PT Bank NTB Syariah is the purchase price plus the profit margin that has been mutually agreed upon between the bank and the customer. 2). Financing products tapak sejahtera iB amanah at PT. Bank NTB Syariah is in accordance with the DSN-MUI fatwa No. 4 of 2000. So it can be stated that in determining the selling price of murabahah products it is in accordance with sharia principles or the DSN-MUI Fatwa